The impact of the euro on financial markets - Lorenzo Cappiello; Peter Hördahl; Arjan Kadareja; Simone Manganelli (European Central Bank (ECB), 2006)
We assess whether the euro had an impact first on the degree of integration of European financial markets, and, second, on the euro area term structure. We propose two methodologies to measure integration: one relies on time-varying GARCH correlations, and the other one on a regression quantile-based codependence measure. We document an overall increase in co movements in both equity and bond euro area markets, suggesting that integration has progressed since the introduction of the euro. However, while the correlations in bond markets reaches almost one for all euro area countries, co-movements in equity markets are much lower and the increase is limited to large euro area economies only. In the second part of the paper, we focus on the asset pricing implications of the euro. Specifically, we use a dynamic no arbitrage term structure model to examine the risk - return trade-off in the term structure of interest rates before and after the introduction of the euro. The analysis shows that while the average level of term premia seems little changed following the euro introduction, the variability of premia has been reduced as a result of smaller macro shocks during the euro period. Moreover, the macro factors that were found to be important in explaining the dynamics of premia before the introduction of the euro continue to play a key role in this respect also thereafter.
Keywords: F36; G12; E43; E44; C22; 330; conditional correlation; euro; financial integration; financial markets; fundamentals; risk premia; Term structure; Volatility; Finanzmarkt; Wirtschaftliche Konvergenz; Eurozone; Volatilität; Zinsstruktur; ARCH-Modell; Risikoprämie; EU-Staaten